Risk Aversion, Supply Response, and the Optimality of Random Prices: A Diagrammatic Analysis - Newbery, David M. G.; Stiglitz, Joseph E. (Quarterly Journal of Economics, 1982)
This paper analyzes the effect of commodity price stabilization on producers and consumers, both in the short run, and in the long run, when producers have adjusted their production decisions to take account of the change in the price distribution. We derive conditions under which (a) both producers and consumers may be better off; and (b) both producers and consumers may be worse off. Moreover, we show that the long-run effects may differ not only quantitatively but also qualitatively from the short-run effects. The anomalous results may occur even with reasonable assumptions concerning production functions and utility functions of producers and consumers.